1996
DOI: 10.1111/j.1365-2184.1996.tb00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic adenoma and adenoid-cystic carcinoma of salivary glands: immunohistochemical assessment of proliferative activity in comparison with flow-cytometric study

Abstract: In this study, 32 pleomorphic adenomas (PAs) and seven adenoid cystic carcinomas (ACCs) were analysed for the evaluation of proliferating cell nuclear antigen (PCNA) indices and flow cytometric variables. Our aim was to assess any possible relationship between these parameters and the clinico-pathological variables and to clarify their histogenesis and reasons for their biological differences. The tumours were divided into three groups, mainly epithelial (E), myxoid (M) and chondroid (C); PCNA labelling index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…Greiner et al4 reported that 95% of the adenoid cystic carcinomas were diploid, and also suggest that SPF may be more useful than ploidy in predicting disease prognosis. Daniele et al21 immunohistochemically assessed the proliferating cell nuclear antigen nuclear expression in a series of 32 pleomorphic adenomas and 7 adenoid cystic carcinomas and suggested that the distinct biologic behavior of the two types of tumors could be explained by differences in their proliferative activity, which were higher in the latter, in keeping with the conclusions of Saka et al33 in their image cytometry study. Using a distinct methodology to estimate cell proliferation, our data do not support this view, because a similar value for the mean SPFs was found in the two types of neoplasms.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Greiner et al4 reported that 95% of the adenoid cystic carcinomas were diploid, and also suggest that SPF may be more useful than ploidy in predicting disease prognosis. Daniele et al21 immunohistochemically assessed the proliferating cell nuclear antigen nuclear expression in a series of 32 pleomorphic adenomas and 7 adenoid cystic carcinomas and suggested that the distinct biologic behavior of the two types of tumors could be explained by differences in their proliferative activity, which were higher in the latter, in keeping with the conclusions of Saka et al33 in their image cytometry study. Using a distinct methodology to estimate cell proliferation, our data do not support this view, because a similar value for the mean SPFs was found in the two types of neoplasms.…”
Section: Discussionmentioning
confidence: 71%
“…Saka et al33 studied a series of 17 mixed tumors by image cytometry and did not find DNA aneuploidy cases. Atula et al34 reported aneuploid clones in 7 of 119 pleomorphic adenomas evaluated, and Daniele et al21 mentioned only 1 of 32 similar cases. These observations were reinforced by data from cytogenetic studies in pleomorphic adenoma,35, 36 which noted specific chromosomal alterations and normal karyotypes associated with either minor or absent quantitative changes of nuclear DNA content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dies steht im Einklang mit anderen durchflusszytophotometrischen Untersuchungen [38,40]. Allerdings berichten einige Studien von gelegentlichem Auftreten aneuploider pleomorpher Adenome [1,6,7], so dass die Entwicklung aneuploider Karyotypen bei diesen Tumoren nicht grundsätzlich ausgeschlossen werden kann. Alle vier Rezidive pleomorpher Adenome dieser Studie waren DNA-diploid.…”
Section: Patienten Und Methodenunclassified
“…Although both tumors originate in the intercalated duct with the same cellular derivation (15) and secretion of proteins of the extracellular matrix (16), they exhibit the characteristic behavior of benign and malignant tumors, respectively, coupled with distinct proliferative activity (17)(18)(19)(20) The objective of this study was to evaluate the role of PCNA and AgNOR in the assessment of salivary gland tumor proliferation using a double staining technique.…”
Section: Introductionmentioning
confidence: 99%